Pedestrian lower limb injury criteria evaluation: A finite element approach - Arnoux, Pierre-Jean; Behr, Michel; Thollon, Lionel; Cardot, Jérome; Cesari, Dominique; Brunet, Christian (European Journal of Computational Mechanics, 2005)
In the field of pedestrian injury biomechanics, knees and lower legs are highly recruited during crash situations, leading to joint damage and bones failures. This paper shows how numerical simulation can be used to complete injury mechanism analysis and then to postulate on a knee injury criteria in lateral impact. It focuses on relationships between ultimate lateral bending and shearing at the knee level and potential ligament damage, based on subsystem experimental tests. These ultimate knee lateral bendings and shearings for potential failure of ligaments (posterior cruciate, medial collateral, cruciates and tibial collateral) were estimated at 16° and 15 mm in pure lateral shearing and bending impact tests respectively. Then this methodology was applied on a full test of pedestrian impact.